THE INFLUENCE OF SERVICE QUALITY, FOOD QUALITY AND DINESCAPE ON CUSTOMER SATISFACTION AT MIE SS PASURUAN - Sulis Edy Wibisono; Liliana Dewi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to analyze the effect of food quality, kualitas pelayananand dinescape on customer satisfaction at Mie SS Pasuruan. The independent variables of this study are kualitas makanan (X1) kualitas pelayanan (X2), Dinescape (X3) the dependent variable of this study is Satisfaction customer (Y1). This research is included in quantitative research because the approach used for research proposals, hypothesis determination, and data analysis up to writing uses aspects that involve measurement, calculation formulas, and data in numerical form. The sample of this research is SS Noodle customers aged over 17 years. by using the heirs theory, the required number of samples is determined to be 190 respondents. The data collection method used was distributing questionnaires to respondents through a print out of the questionnaire. The data that has been collected was analyzed usinf spss 15 by testing data validity, data reliability, multiple linear regression tests, t tests and r square tests. The results of this study indicate that food quality, service quality and dinscape have a significant effect on customer satisfaction